Regional Dynamics and Rural Development in Romania’s South-East Region 2 - Daniela Lavinia Balasan; Dragoș Horia Buhociu (Journal of Agriculture and Rural Development Studies, 2025)
This article explores the socio-economic dynamics and structural conditions shaping rural development in South-East Region 2 of Romania. Comprising six counties (Brăila, Buzău, Constanța, Galați, Tulcea, and Vrancea), the region exhibits significant disparities in development, infrastructure, and access to skilled labor. The analysis highlights the fundamental pillars of rural development: human capital, infrastructure, local governance, and access to financing. It also discusses current challenges such as population decline, youth migration, and limited institutional capacity. Based on these findings, the paper proposes strategic directions for revitalizing rural areas through the development of local economies, vocational education, and integrated funding mechanisms. Emphasis is placed on aligning public investment with real community needs, strengthening partnerships, and promoting sustainable, locally adapted development models.